Serum hCG Levels following the Ovulatory Injection: Associations with Patient Weight and Implantation Time. (26th October 2015) - Noorhasan, Dorette J.; McGovern, Peter G.; Cho, Michael; Seungdamrong, Aimee; Ahmad, Khaliq; McCulloh, David H.
Abstract : Objective . To test if serum hCG levels the morning after the ovulatory hCG injection correlate with (1) retrieval efficiency, (2) oocyte maturity, (3) embryo quality, (4) pregnancy, and/or (5) time to implantation in patients undergoing in vitro fertilization (IVF) with intracytoplasmic sperm injection (ICSI). Design . Retrospective cohort analysis. Setting . University-based IVF clinic. Patient(s) . All IVF/ICSI cycles from April 2005 to February 2008 whose hCG administration was confirmed (n = 472 patients). Intervention(s) . Serum hCG was measured the morning following the ovulatory injection, on the 16th day following retrieval, and repeated on day 18 for those with positive results. Main Outcome Measure(s) . Number of follicles on the day of hCG injection, number of oocytes retrieved, maturity of oocytes, embryo quality, pregnancy outcome, and time to implantation. Result(s) . hCG levels did not correlate with retrieval efficiency, oocyte maturity, embryo quality, or pregnancy. Postinjection hCG levels were inversely associated with patient weight and time to implantation. Conclusion(s) . No correlation was found between hCG level and any parameter of embryo quality. Patient weight affected hCG levels following hCG injection and during the early period of pregnancy following implantation. No association between postinjection hCG level and time of implantation (adjusted for patient weight) was apparent.